A novel model for the lift force acting on a prolate spheroidal particle in arbitrary non-uniform flow. Part II. Lift force taking into account the non-streamwise flow shear. (February 2019) - Cui, Yan; Ravnik, Jure; Verhnjak, Ožbej; Hriberšek, Matjaž; Steinmann, Paul
Highlights: A new generic method for the computation of the Saffman-type lift forces acting on a rigid particle in arbitrary non-uniform flows is presented. The method computes the shear-induced lift force taking into account also non-streamwise flow shear. A novel shear-induced lift force model is developed for prolate spheroidal particles by using this method. The accuracy and reliability of the proposed shear-induced lift model are verified and validated in Poiseuille and lid-driven cavity flows by comparing it with other Saffman-type lift force models. Abstract: The present contribution is the second part of a two-part research work presenting a generic method to extend lift force models that were originally devised for single linear shear flow to arbitrary flow conditions. The method can be applied to the computation of lift forces exerted on prolate spheroidal particles (or fibres) in arbitrary non-uniform flows. The method proposed in the Part I calculates the lift force arising from the dominant streamwise flow shear. In Part II the influence of the non-streamwise flow shear on the lift force is also taken into account. The present method assumes that the particle slip velocity is parallel to the fluid velocity along the particle trajectory. The novelty in the presented method is the computation of the shear lift force model for prolate spheroidal particles taking into account also non-streamwise flow shear. The accuracy of the novel shear lift force model for prolate spheroidal particles is verified by comparing it with the lift force model proposed in Part I via simulating the axial migration of a prolate spheroidal particle in the Poiseuille flow. In order to validate the ability of the present method for capturing the lift component arising from non-streamwise flow shear, the lift force model is compared with established generalised Saffman-type lift models by simulating the motion of a particle in lid-driven cavity flow. The computational results demonstrate that the present lift force model for prolate spheroidal particles is applicable in flow cases with streamwise and non-streamwise flow shear, even if some (reasonably small) accuracy for the case of the streamwise-only shear is lost.